Effect of grazing alfalfa on α-tocopherol content and FA composition in Longissimus and Semitendinosus muscles of light lambs - Molino F.; Blanco M.; González-Calvo L.; Ripoll G.; Calvo J.H.; Joy M. (Forage resources and ecosystem services provided by Mountain and Mediterranean grasslands and rangelands, 2014)
Grazing can increase α-tocopherol content in the lamb muscle without additional expenses compared with tocopheryl acetate supplementation and modify the fatty acid (FA) profile. The aim of the study was to compare the effect of alfalfa grazing on α-tocopherol and FA composition of Longissimus thoracis (LT) and Semitendinosus (ST) muscles. Twenty single reared male lambs of Rasa Aragonesa breed were used. A group of weaned lambs was indoors and fed concentrate and a group of suckling lambs was grazing alfalfa continuously with their dams. The LT and ST muscles were extracted to determine α-tocopherol content and FA composition. In both muscles, grazing lambs had more than 2-fold higher α-tocopherol content, C18:2n-6tt, C18:3n-3, C20:5n-3, C22:5n-3, C22:6n-3 and total n-3 FA contents (P<0.001) but lower n-6:n-3 ratio (P<0.001) than concentrate-fed lambs. In both muscles, grazing lambs had lower Monounsaturated FA than concentrate-fed lambs. Generally, grazing had a greater impact on n-3 FA and α-tocopherol content in ST than in LT muscle. Grazing improved the n-6:n-3 ratio and could increase the meat shelf-life. The α-tocopherol content and individual n-3 FA could be used to authenticate forage intake.
Joint Meeting of the "Mountain Pastures, Mediterranean Forage Resources (FAO/ESCORENA-CIHEAM) and Mountain Cheese" Network, 2014/06/24-26, Clermont-Ferrand (France)